Shall we go «Ad Aquas»? Putting Roman healing spas on the map = ¿Nos vamos «Ad Aqvas»?: Poniendo los balnearios romanos en el mapa - Silvia González Soutelo (Espacio, Tiempo y Forma. Serie I, Prehistoria y Arqueología, 2019)
Bath constructions are today among other monuments one of the better preserved and studied monuments of the Roman Empire. Nevertheless, there remains a significant research gap as to the nature of water exploited within. The mineral-medicinal waters, in fact, conditioned not only the location, but also the function and, consequently, the architecture of these features. Hence, one of the main objectives of our current study is to highlight the main architectonic and functional characteristics of these bathing complexes. This paper thus advances a first distribution map specifically defining the spread of the better preserved and/or better documented spas using mineral-medicinal waters in the Roman Empire (henceforth referred to as healing or thermal spas/baths). This study also advances the current state of research on the question, some of the main characteristics of these types of complexes, as well as some of the drawbacks to their study.